Assessment of Operational, Environmental and Social Performance of Container Ports in Türkiye - Esra Yıldırım Söylemez (Verimlilik Dergisi)
ABSTRACTPurpose: This study aims to reveal the sustainability orientations of container port facilities operating in Turkey through sustainability reports and to evaluate the performance of their operational, environmental and social dimensions both separately and in an integrated manner (Environmental, Social, Operational-ESO).Methodology: Sustainability orientations of container port facilities were subjected to qualitative assessment through examination of web pages and sustainability reports. The data obtained through document scanning regarding operational, environmental, and social performance indicators revealed by researching the relevant literature were analyzed using the MULTIMOORA method. The Rank Position Method was used in the performance ranking of port facilities.Findings: The results show that 18% of the container service port facilities publish independent sustainability reports. There are deficiencies in the environmental and especially social performance indicators taken into account in the sustainability reports. Among the port facilities examined, Mersin International Port, which has the highest operational performance, is also ranked as the facility with the lowest integrated performance (ESO). The port facility with the highest integrated performance (ESO) was Socar.Originality: The study contributes to filling the gap in the literature regarding the evaluation of environmental, social and operational performance of container ports in Turkey with the MULTIMOORA method. More importantly, the integrated examination of relevant performance dimensions represents the originality of this study.